Resource-constrained project scheduling: A survey of recent developments - HERROELEN, Willy (Institutional Knowledge at Singapore Management University, 1996)
Resource-constrained project scheduling involves the scheduling of project activities subject to precedence and resource constraints in order to meet the objective(s) in the best possible way. The area covers a wide variety of problem types. The objective of this paper is to provide a survey of what we believe are the important recent developments in the area. Our main focus will be on the recent progress made in and the encouraging computational experience gained with the use of optimal solution procedures for the basic resource-constrained project scheduling problem (RCPSP) and important extensions. We illustrate how the branching rules, dominance and bounding arguments of a new depth- first branch-and-bound procedure can be extended to a rich variety of related problems: the generalized resource-constrained project scheduling problem, the resource-constrained project scheduling problem with generalized precedence relations, the preemptive resource-constrained project scheduling problem, the resource availability cost problem, and the resource-constrained project scheduling problem with various time/resource(cost) trade-offs and discounted cash flows.